Praxis der Telemedizin in Deutschland heute - Schenkel, Johannes (DMW - Deutsche Medizinische Wochenschrift, 2017)
The health care system of Germany approved a marginal number of telemedicine applications for reimbursement. However Teleradiology and Telestroke networks are well adopted in Germanys hospitals. Heart failure is the main indication for remote patient management and therefore a field of intense research in Germany. In almost every medical field telemedicine undergoes research and development. The lack of evidence in the field of telemedicine is due to the complexity of these interventions. Evaluation needs more resources and different trial designs compared to RCTs in pharmaceutical trials. A large scale funding program (Innovationsfonds) in Germany encompasses telemedicine and outcomes research. Mobile health apps are a new and expanding field in healthcare. Health apps are potentially beneficial in many health care areas, although there is little scientific evidence available. From a legal perspective data protection and privacy and the classification of health apps as medical devices are important topics.
Keywords: eHealth; Telemedizinische Patientenversorgung; Remote-Patient-Management; Berufsrecht; Gesundheits-Apps